MAX-DOAS measurements in southern China: retrieval of aerosol extinctions and validation using ground-based in-situ data - Li, Xiaoqiang; Brauers, T.; Shao, M.; Garland, R. M.; Wagner, T.; Deutschmann, Tim; Wahner, A. (Atmospheric chemistry and physics, 2010)
We performed MAX-DOAS measurements during the PRiDe-PRD2006 campaign in the Pearl River Delta region 50 km north of Guangzhou, China, for 4 weeks in June 2006. We used an instrument sampling at 7 different elevation angles between 3° and 90°. During 9 cloud-free days, differential slant column densities (DSCDs) of O4 (O2 dimer) absorptions between 351 nm and 389 nm were evaluated for 6 elevation angles. Here, we show that radiative transfer modeling of the DSCDS can be used to retrieve the aerosol extinction and the height of the boundary layer. A comparison of the aerosol extinction with simultaneously recorded, ground based nephelometer data shows excellent agreement.
Gesehen am 14.03.2023